1953
DOI: 10.1111/j.1476-5381.1953.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine‐like Actions in Auricles and Blood Vessels After Denervation

Abstract: The work to be described in this paper is a continuation of observations made on the action of nicotine and acetylcholine in the isolated auricles of the rabbit heart and in the perfused vessels of the rabbit ear (Kottegoda, 1953a(Kottegoda, , 1953b. Nicotine and acetylcholine were found to stimulate the auricles in the presence of atropine, and the stimulant action was blocked by hexamethonium. Similarly nicotine was found to constrict the vessels of the rabbit ear; acetylcholine in the presence of atropine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1957
1957
1979
1979

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Similar actions of nicotine have previously been described on the smooth muscle in the vessels of the frog's hind legs (Loewi, 1937), on the smooth muscle in the vessels of the rabbit's ear (Ginzel & Kottegoda, 1953) and in the walls of the bronchi (D. F. Hawkins & W. D. M. Paton, unpublished), structures which are normally assumed to be free from ganglion cells. It seems almost certain that the responses of the isolated nictitating membrane to nicotine and tetramethylammonium are produced indirectly through the release of adrenaline and/or noradrenaline.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar actions of nicotine have previously been described on the smooth muscle in the vessels of the frog's hind legs (Loewi, 1937), on the smooth muscle in the vessels of the rabbit's ear (Ginzel & Kottegoda, 1953) and in the walls of the bronchi (D. F. Hawkins & W. D. M. Paton, unpublished), structures which are normally assumed to be free from ganglion cells. It seems almost certain that the responses of the isolated nictitating membrane to nicotine and tetramethylammonium are produced indirectly through the release of adrenaline and/or noradrenaline.…”
Section: Discussionsupporting
confidence: 72%
“…Microscopical sections did, however, show large numbers of fine nerve fibres lying amongst the muscle and it seems most probable that these are the structures stimulated by nicotine and tetramethylammonium and are, in fact, the postganglionic nerve fibres to the muscle. These substances might stimulate either the trunk or the fine endings of these nerves and possibly produce a local axon reflex, as was suggested by Ginzel & Kottegoda (1953) when they investigated the action of nicotine in the vessels of the rabbit's ear. Although Evans & Schild (1953a, b) have demonstrated instances in which nicotine appears to act directly on smooth muscle, it is difficult to believe that this occurs in the normal isolated nictitating membrane.…”
Section: Discussionmentioning
confidence: 92%
“…A stimulating action on the isolated rabbit or cat heart by ganglionic stimulants such as nicotine and ACh after atropine was described by Hoffmann, Hoffmann, Middleton and Talesnik (1945) and more recently on the isolated rabbit auricles by Kottegoda (1953) and Ginzel and Kottegoda (1953). The latter authors found that this effect could be blocked by HMI, and assumed the presence of peripheral sympathetic ganglia within the auricular tissue.…”
Section: Effect On Gastric Hcl Secretion Of Ratsmentioning
confidence: 93%
“…Moreover, the fact that tachycardia can be induced by acetylcholine or by vagal stimulation in the atropinized heart (Jourdan & Nowak, 1936; Kabat, 1939;Brown & Maycock, 1942; Hoffmann, Hoffmann, Middleton & Talesnik, 1945;Heymans & Bennati, 1949) suggests the possibility that acceleration occurs through the activation of sympathetic structures (ganglia and/or chromaffin tissue) located in the myocardium (Heymans & Bennati, 1949;Ginzel & Kottegoda, 1953; Burn, Leach, Rand & Thompson, 1959). Other findings suggesting a possible peripheral activation of adrenergic structures by acetylcholine have been presented by Burn & Rand (1959).…”
mentioning
confidence: 99%